2015
DOI: 10.1016/j.neuron.2015.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Rhythms Link Prefrontal Interneuron Dysfunction with Cognitive Inflexibility in Dlx5/6+/− Mice

Abstract: SUMMARY Abnormalities in GABAergic interneurons, particularly fast-spiking interneurons (FSINs) that generate gamma (γ; ~30-120 Hz) oscillations, are hypothesized to disrupt prefrontal cortex (PFC)-dependent cognition in schizophrenia. Although γ rhythms are abnormal in schizophrenia, it remains unclear whether they directly influence cognition. Mechanisms underlying schizophrenia's typical post-adolescent onset also remain elusive. We addressed these issues using mice heterozygous for Dlx5/6, which regulate G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
361
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 314 publications
(388 citation statements)
references
References 39 publications
27
361
0
Order By: Relevance
“…Network hyperexcitability and epileptiform events have been observed in most mouse models of AD (Palop et al, 2007, 2011; Busche et al, 2008; Palop and Mucke, 2009; Harris et al, 2010; Roberson et al, 2011; Yan et al, 2012; Busche and Konnerth, 2016) and in AD patients using high resolution recordings (Lam et al, 2017). Hypersynchronous network activities have been shown to emerge during reduced gamma oscillation, which is a rhythm that depends on the activities of fast-spiking PV INs and contributes to cognitive functions (Cardin et al, 2009; Sohal et al, 2009; Buzsáki and Wang, 2012; Sohal, 2012; Cho et al, 2015). Specifically, PV IN defects due to a reduced expression of voltage-gated sodium channels Nav1.1 were found in hAPPJ20 mice, and reversing the Nav1.1 reduction by Nav1.1-BAC bacterial rescued PV IN synaptic currents and gamma oscillations and reduced network hypersynchrony and memory deficits in these mice (Verret et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Network hyperexcitability and epileptiform events have been observed in most mouse models of AD (Palop et al, 2007, 2011; Busche et al, 2008; Palop and Mucke, 2009; Harris et al, 2010; Roberson et al, 2011; Yan et al, 2012; Busche and Konnerth, 2016) and in AD patients using high resolution recordings (Lam et al, 2017). Hypersynchronous network activities have been shown to emerge during reduced gamma oscillation, which is a rhythm that depends on the activities of fast-spiking PV INs and contributes to cognitive functions (Cardin et al, 2009; Sohal et al, 2009; Buzsáki and Wang, 2012; Sohal, 2012; Cho et al, 2015). Specifically, PV IN defects due to a reduced expression of voltage-gated sodium channels Nav1.1 were found in hAPPJ20 mice, and reversing the Nav1.1 reduction by Nav1.1-BAC bacterial rescued PV IN synaptic currents and gamma oscillations and reduced network hypersynchrony and memory deficits in these mice (Verret et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, using optogenetic tools in animals, it has recently been demonstrated that gamma oscillatory activity in the pre‐frontal cortex controlled by FSIs is important for cognitive performance (Cho et al . 2015, Kim et al . 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Dlx5/6(+/-) mice show a reduced cognitive flexibility that seemingly results from an abnormal pattern of γ rhythms caused by abnormalities in GABAergic interneurons; this phenotype recapitulates some clinical findings in SZ patients [Cho et al, 2015]. During language processing, γ rhythms are hypothesized to generate syntactic objects before β holds them in memory and they also contributes to lexical processing [see Murphy, 2015, for details].…”
Section: Sz and (The Evolution Of) Human Languagementioning
confidence: 93%